Many Unions, One Estimate? Disaggregating the Currency Union Effect on Trade - Kopecky, Joseph (My University, 2023)
A large literature estimates the impact of currency unions on trade. Often ignored in these estimates are the dramatic differences in the characteristics of countries adopting common currencies, hidden by aggregation into a single currency union effect. I show that currency unions have substantial differences in their observable characteristics, relative to non-unions, making them a poor comparison group for estimation of policy treatment. Further, these differences are heterogeneous across individual currency unions, making one aggregate estimate likely inappropriate. Using inverse propensity score methods, I find that adjusting these gravity equation estimates to account these differences, both via weighting and via sample adjustment, meaningfully impacts the estimated policy effects. I find a wide range of currency union effects across individual, disaggregated, currency unions. My results suggest that future work on currency unions, and other macroeconomic policies, should be careful to check for such underlying heterogeneity when estimating policy effects.
PUBLISHED
Keywords: Currency unions; Trade; Propensity scores; Gravity; International Development; International Integration; International Trade & Finance; International economics, finance, trade and development; Macroeconomics, open economy, international; Trade Policy